Conscientização para adoção de boas práticas sanitárias em bem-estar animal no manejo das mastites do rebanho bovino: Miriam Yumi Makatu. - - Makatu, Miriam Yumi [UNESP] (2015)
Aimed at verifying whether the adoption of good agricultural practices is a good tool for the identification of animals with bovine mastitis, and educating the producer of rural settlements about the importance of implementing good agricultural practices related to welfare. The producers were oriented and received educational material and utensils made from recyclable material to the achievement of good health practices. For evaluation of the physiological profile, biological samples such as blood, feces and milk were collected, and for the assessment of sanitation and welfare, a questionnaire was employed. A total of 79 mammary quarters from 20 cows were evaluated. Of the 36 negative quarters for California Mastitis Test, 12 were positive for bacteria, with Staphylococcus being the most frequently isolated. The results indicated that animal welfare was compromised by the incidence of subclinical mastitis, infestation with ectoparasites and the absence of prophylactic measures. It is concluded that the use of good agricultural practices is suitable for the identification of bovine mastitis, however, there is lack of knowledge regarding good practices, mainly related to preventive management and awareness of producers about the importance of implementing good agricultural practices in the dairy activity, which are key to improving animal welfare conditions, productivity and quality of milk